Association of Insulin Resistance with Glucose and Lipid Metabolism: Ethnic Heterogeneity in Far Western China - Yi-Zhong Yan; Ru-Lin Ma; Jing-Yu Zhang; Jia He; Jiao-Long Ma; Hong-Rui Pang; La-Ti Mu; Yu-Song Ding; Heng Guo; Mei Zhang; Jia-Ming Liu; Dong-Sheng Rui; et al. (Mediators of Inflammation)
Objective. To study the relationships between IR and glucose and lipid metabolism in far western China and these relationships’ ethnic heterogeneity. Methods. From the baseline survey, 419 Uygur cases, 331 Kazak cases, and 220 Han cases were randomly selected, resulting in a total of 970 cases for study. FINS concentration was measured by radioimmunoassay. Results. (1) In the Kazak population, IR was correlated with hyperglycemia; high levels of TC, TG, and LDL-C; and low levels of HDL-C and abdominal obesity (all P<0.05). (2) In the Uygur population, the influence of IR on hyperglycemia and abdominal obesity was the greatest. In the Kazak population, IR was associated with hyperglycemia most closely. In the Han population, IR may have had an impact on the incidence of low HDL-C levels. (3) After adjusting for sex, age, smoking status, and alcohol consumption, IR was still associated with anomalies in the metabolism of the Uygur, Kazak, and Han populations. Conclusion. IR was involved in the process of glucose and lipid metabolism, and its degree of involvement differed among the ethnicities studied. We could consider reducing the occurrence of abnormal glucose and lipid metabolism by controlling IR and aiming to reduce the prevalence of metabolic syndrome and related diseases.